UNDERSTANDING OF SYMBOLIC VIOLENCE IN REALIZING THE CONDUCIVE EDUCATIONAL ECOSYSTEM (STUDY ON MAN KOTA BATU) - Amirulloh, Sabilla (University of Muhammadiyah Malang, 2019)
The phenomenon of violence in the school environment is still happening. Such violence may be physical violence, verbal violence, psychic violence, and symbolic violence. Various forms of violence have been understood as a school effort to discipline students. However, that violence may potentially impact the educational environment to be non-conducive. This study aims to explore more deeply about the ecosystem in Madrasah Aliyah Negeri Kota Batu. To achieve that goal, this research is done by using a qualitative research approach. Subjects of this study were teachers and students who were in the arena of symbolic violence, namely in the school environment. Data collection uses observation, interview, and documentation. The data obtained were analyzed using technical analysis from Miles and Huberman with data condensation, data display, and conclusion. Test data validity uses data triangulation and method triangulation. This study was analyzed using the perspective of symbolic violence of Pierre Bourdieu. The results of this study indicate that there is no intention from the school to commit violence on the basis of their power. The assertive action was taken solely as a disciplining process to learners. The action is aimed at students to have a ?moral honor? that is useful to them and create a conducive educational ecosystem. Although sometimes get a reaction from learners but this action they can understand as an action that is naturally done by the school in the face of irregularities committed by some learners.